Ageing modifies acute resting blood pressure responses to incremental consumption of dietary nitrate: a randomised, cross-over clinical trial. Issue 3 (14th February 2023) - Capper, Tess; Clifford, Tom; Taylor, Guy; Iqbal, Wasim; West, Daniel; Stevenson, Emma; Siervo, Mario
Abstract: Beetroot (BR) is a rich source of nitrate (NO3 -) that has been shown to reduce blood pressure (BP). Yet, no studies have examined the vascular benefits of BR in whole-food form and whether the effects are modified by age. This study was a four-arm, randomised, open-label, cross-over design in twenty-four healthy adults (young n 12, age 27 ± 4 years, old n 12, age 64 ± 5 years). Participants consumed whole-cooked BR at portions of (NO3 - content in brackets) 100 g (272 mg), 200 g (544 mg) and 300 g (816 mg) and a 200-ml solution containing 1000 mg of potassium nitrate (KNO3 ) on four separate occasions over a 4-week period (≥7-d washout period). BP, plasma NO3 - and nitrite (NO2 -) concentrations, and post-occlusion reactive hyperaemia via laser Doppler, were measured pre- and up to 5-h post-intervention. Data were analysed by repeated-measures ANOVA. Plasma NO2 - concentrations were higher in the young v . old at baseline and post-intervention ( P < 0·05). All NO3 - interventions decreased systolic and diastolic BP in young participants ( P < 0·05), whereas only KNO3 (at 240–300 min post-intake) significantly decreased systolic (–4·8 mmHg, −3·5 %, P = 0·024) and diastolic (–5·4 mmHg, −6·5 %, P = 0·007) BP in older participants. In conclusion, incremental doses of dietary NO3 - reduced systolic and diastolic BP in healthy young adults whereas in the older group a significant decrease was only observed with the highest dose. The lower plasma NO2 - concentrations in older participants suggest that there may be mechanistic differences in the production of NO from dietary NO3 - in young and older populations.